Stomatal and pavement cell density linked to leaf internal CO2 concentration - Santrůček, Jiří; Vráblová, Martina; Simková, Marie; Hronková, Marie; Drtinová, Martina; Květoň, Jiří; Vrábl, Daniel; Kubásek, Jiří; Macková, Jana; Wiesnerová, Dana; Neuwithová, Jitka; Schreiber, Lukas (Annals of botany, 2014)
BACKGROUND AND AIMS: Stomatal density (SD) generally decreases with rising atmospheric CO2 concentration, Ca. However, SD is also affected by light, air humidity and drought, all under systemic signalling from older leaves. This makes our understanding of how Ca controls SD incomplete. This study tested the hypotheses that SD is affected by the internal CO2 concentration of the leaf, Ci, rather than Ca, and that cotyledons, as the first plant assimilation organs, lack the systemic signal. METHODS: Sunflower (Helianthus annuus), beech (Fagus sylvatica), arabidopsis (Arabidopsis thaliana) and garden cress (Lepidium sativum) were grown under contrasting environmental conditions that affected Ci while Ca was kept constant. The SD, pavement cell density (PCD) and stomatal index (SI) responses to Ci in cotyledons and the first leaves of garden cress were compared. (13)C abundance (δ(13)C) in leaf dry matter was used to estimate the effective Ci during leaf development. The SD was estimated from leaf imprints. KEY RESULTS: SD correlated negatively with Ci in leaves of all four species and under three different treatments (irradiance, abscisic acid and osmotic stress). PCD in arabidopsis and garden cress responded similarly, so that SI was largely unaffected. However, SD and PCD of cotyledons were insensitive to Ci, indicating an essential role for systemic signalling. CONCLUSIONS: It is proposed that Ci or a Ci-linked factor plays an important role in modulating SD and PCD during epidermis development and leaf expansion. The absence of a Ci-SD relationship in the cotyledons of garden cress indicates the key role of lower-insertion CO2 assimilation organs in signal perception and its long-distance transport.
Keywords: Helianthus; Lepidium sativum; životní prostředí; Cell Count; Fagus sylvatica; Arabidopsis thaliana; Arabidopsis; Environment; Fagus; pavement cells; Plant Stomata; Helianthus annuus; Lepidium; leaf internal CO2; kotyledon; průduchy rostlin; cotyledons; počet buněk; dehydratace; Stomatal density; Carbon Dioxide; 13C discrimination; Dehydration; oxid uhličitý; stomata development; Cotyledon; buk (rod)